Exploratory study on consumer emotions during sales - Bong, Cindy Feng Ling (2008)
This research attempts to explore Consumer Emotions during Sales in Singapore, specifically attempting to identify positive and negative emotions experienced. The VALs model and some other emotion models were used in this research.